Carbon quantum dot coated mixed-phase sodium-ion battery positive electrode material as well as preparation method and application thereof

By adopting a mixed phase structure coated with carbon quantum dots in the positive electrode material of sodium ion battery, the problems of unstable layered oxide structure and slow diffusion rate of sodium ions are solved, and the rate performance and cycle stability of the material are significantly improved.

CN119812236AActive Publication Date: 2025-04-11HEFEI GUOXUAN HIGH TECH POWER ENERGY

Patent Information

Application Number
CN202411378433.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-04-11
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The layered oxide structure of the positive electrode materials of existing sodium ion batteries is unstable, and the sodium ion diffusion rate is slow, resulting in poor rate performance and poor cycle stability.

Method used

The P2 phase and O3 phase sodium ion battery positive electrode material coated with carbon quantum dots is prepared by mixing and calcining the nickel-ferromanganese-based hydroxide precursor with a sodium source and dopant, and then mixing it with the carbon quantum dots uniformly in the solvent to form a mixed phase structure coated by carbon quantum dots.

Benefits of technology

The conductivity of the material is improved, the side reaction with the electrolyte is suppressed, and the rate performance and cycle stability are significantly improved, so that the material has ultra-high rate performance and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812236A_ABST
    Figure CN119812236A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon quantum dot coated mixed-phase sodium ion battery positive electrode material as well as a preparation method and application thereof, and belongs to the technical field of sodium ion batteries. The positive electrode material disclosed by the invention is a carbon quantum dot-coated mixed-phase nickel-iron-manganese-based sodium ion battery positive electrode material, and the mixed-phase structure is formed by mixing P2 and O3 phases; carbon quantum dot coating improves the overall conductivity of the material and inhibits side reaction between the material and electrolyte, so that the positive electrode material has ultrahigh rate capability and cycling stability and can be used as a sodium ion battery positive electrode material; according to the method disclosed by the invention, coating is carried out in a liquid-phase environment, so that uniform coating of the carbon quantum dots on the surface of the mixed-phase sodium-ion battery positive electrode material is ensured, the method is simple, and the coating effect is good; and the obtained carbon quantum dot coated mixed-phase sodium ion battery positive electrode material is good in crystallinity and stable in structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material, a preparation method and an application thereof. Background Art

[0002] Sodium-ion batteries belong to the category of secondary rechargeable batteries. As one of the energy storage systems with the highest energy conversion efficiency, secondary batteries have received more and more attention. Among the many secondary battery systems, sodium-ion batteries have the advantages of abundant reserves of raw sodium sources, wide distribution, and low cost. Sodium and aluminum do not undergo alloying reactions, and cheap aluminum foil can be used as the current collectors for both the positive and negative electrodes of sodium-ion batteries, which can further reduce costs and eliminate over-discharge problems. Sodium-ion batteries have excellent rate performance and high and low temperature performance; sodium-ion batteries have the advantages of no fire, no explosion, and good safety performance in safety tests. Therefore, when the energy density requirement is not high, sodium-ion batteries are an excellent substitute.

[0003] One of the key components of sodium-ion batteries is the cathode material. Currently, the cathode materials for sodium-ion batteries include metal layered oxides, polyanions, Prussian blue, etc. Among them, layered oxides have a high theoretical capacity and are easy to synthesize, making them one of the most promising cathode materials for sodium-ion batteries. Layered oxide sodium battery cathode materials have a relatively stable charging and discharging platform, are low-cost, and are environmentally friendly, making them a hot topic in current research. How to improve the cycle stability of layered oxide cathode materials and increase their energy density is a current scientific frontier issue.

[0004] Due to Na + Compared to Li + With a larger ionic radius (1.02Å), its embedding and extraction in the tightly packed layered transition metal oxide material causes a significant change in the structure of the positive electrode material, resulting in the gradual disintegration of the material structure with the increase in the number of charge and discharge cycles, which is manifested in the poor electrochemical stability of the active material and the rapid decay of capacity. Therefore, researchers are committed to developing new layered structure systems to enhance the Na + According to the reversibility of Na + The stacking order of the occupancy and oxygen atomic layers can divide the layered oxides into P2, P3, O2, and O3 phase structures. +The diffusion channel barrier is smaller and the material has fewer structural phase changes, so the rate performance and cycle stability of the material are better, but the specific capacity and average voltage of the P-phase material are lower than those of the O-phase layered oxide material. Therefore, most single-crystal pure-phase layered metal oxide sodium ion battery positive electrode materials exhibit poor electrochemical performance. Recently, the method of utilizing the mixed phase synergy in layered transition metal oxide sodium ion battery positive electrode materials and combining the electrochemical performance advantages of different structures has attracted people's attention. At present, the performance improvement through the mixed phase of the two-phase layered composite material P2 and O3 is not significant. The performance of the prepared materials mostly shows the effect of taking advantage of each other's strengths and weaknesses, and cannot comprehensively improve the performance of the materials. How to effectively improve the ion diffusion rate and electronic conductivity of the mixed-phase sodium ion battery positive electrode material, thereby improving its rate performance and charge and discharge cycle stability, is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0005] In view of the problems in the prior art that the layered oxide structure of the positive electrode material of the sodium ion battery is unstable and the sodium ion diffusion rate is slow, resulting in poor rate performance and poor cycle stability, the present invention provides a carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material and a preparation method and application thereof.

[0006] The present invention first provides a method for preparing a carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material, which is characterized by comprising the following steps: (1) A nickel-iron-manganese-based hydroxide precursor, a sodium source and a dopant are mixed and calcined, and P2 phase and O3 phase sodium ion battery positive electrode materials are prepared by setting different proportions of the sodium source; (2) mixing the P2 phase and O3 phase sodium ion battery positive electrode materials to obtain a mixed phase sodium ion battery positive electrode material; (3) Dissolving the carbon quantum dot powder and the mixed-phase sodium ion battery positive electrode material in a solvent and stirring the mixture to obtain a solid which is the mixed-phase sodium ion battery positive electrode material coated with the carbon quantum dots.

[0007] The positive electrode material of the present invention is a mixed-phase nickel-iron-manganese-based sodium ion battery positive electrode material coated with carbon quantum dots, and its mixed-phase structure is a mixture of P2 and O3 phases; the carbon quantum dot coating improves the overall conductivity of the material and inhibits its side reaction with the electrolyte, so that the positive electrode material has ultra-high rate performance and cycle stability, and can be used as a positive electrode material for sodium ion batteries.

[0008] The method for preparing the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material, in step (1), when the molar ratio of the nickel-iron-manganese-based hydroxide precursor to the sodium in the sodium source is 1: (0.5-0.7), the P2 phase sodium ion battery positive electrode material is prepared; when the molar ratio of the nickel-iron-manganese-based hydroxide precursor to the sodium in the sodium source is 1: (0.8-1), the O3 phase sodium ion battery positive electrode material is prepared; The sodium source is sodium carbonate and / or sodium hydroxide; The dopant is a metal oxide of at least one of Al, Ca, Mg, Ti, Cu, Zn and Zr; specifically, TiO2 and ZrO2; The amount of the dopant added is 500-5000ppm of the mass of the nickel-iron-manganese-based hydroxide precursor; Specifically, when the dopants are TiO2 and ZrO2, taking the mass of the nickel-iron-manganese-based hydroxide precursor as a reference, the Ti element is doped at 2000 ppm and the Z element r is doped at 2000 ppm.

[0009] In the method for preparing the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material, in step (1), the calcination temperature is 500-1100°C; specifically, it can be 800-1000°C; more specifically, it can be 800°C, 850°C, 900°C, 950°C or 1000°C; The calcination is carried out in an air atmosphere; The calcination time is 8-15 hours, specifically 15 hours; the calcination heating rate is 2-10°C / min, specifically 2°C / min.

[0010] In the above-mentioned method for preparing the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material, in step (2), the mass ratio of the P2 phase and the O3 phase sodium ion battery positive electrode material is (0.2~2):1; specifically, it can be 0.25:1; In step (3), based on the total mass of the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material, the carbon content contributed by the carbon quantum dots is 0.01wt% to 0.3wt%, specifically 0.1%; The solvent is anhydrous ethanol and / or tetrahydrofuran; The stirring time is 0.5 to 2 hours; The carbon quantum dot powder and the mixed-phase sodium ion battery positive electrode material are dissolved in a solvent, wherein the solid content is 10wt% to 90wt%, specifically 50wt%.

[0011] The preparation method of the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material, the specific steps of step (3) are as follows: dissolving the carbon quantum dot powder and the mixed-phase sodium ion battery positive electrode material in a solvent, introducing nitrogen gas for stirring, allowing natural sedimentation, and drying the obtained solid to obtain the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material; Specifically, the nitrogen introduction rate is 0.5-20 L / min, specifically 10 L / min; the drying temperature is 100-200°C.

[0012] In the above-mentioned method for preparing the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material, the molar ratio of nickel element, iron element and manganese element in the nickel-iron-manganese-based hydroxide precursor is 1:0.5~1.5:0.5~1.5; specifically, it can be 1:1:1; The nickel-iron-manganese-based hydroxide precursor is prepared by a coprecipitation method; specifically, the nickel source is one or two of nickel sulfate, nickel chloride, nickel acetate or nickel nitrate; the iron source is one or two of ferrous sulfate, ferrous chloride, ferrous acetate or ferrous nitrate; the manganese source is one or two of manganese sulfate, manganese chloride, manganese acetate or manganese nitrate; the complexing agent is ammonia water or ammonium sulfate; the precipitant is sodium hydroxide solution; the reaction temperature is 50-60°C, the start-up bottom liquid pH=11.0-11.9; the concentration of the complexing agent is 2-8g / L; the concentration of the precipitant is 2-4mol / L; the concentration of the metal salt solution is 1-2mol / L; the flow rates of the precipitant and the metal salt solution are both 2-10L / h; In the above-mentioned method for preparing the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material, the carbon quantum dots are prepared by a hydrothermal method; Specifically, the method for preparing the carbon quantum dots comprises the following steps: preparing at least one of citric acid, ethylenediaminetetraacetic acid and L-cysteine ​​into an aqueous solution, and performing a hydrothermal reaction to obtain the carbon quantum dots.

[0013] In the above-mentioned method for preparing the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material, the mass percentage concentration of the aqueous solution is 20% to 80%; The temperature of the hydrothermal reaction is 150-200° C. and the time is 2-15 hours.

[0014] In the method for preparing carbon quantum dots, there are steps of crystallization concentration and drying after the hydrothermal reaction.

[0015] The present invention also provides a mixed-phase sodium ion battery positive electrode material coated with carbon quantum dots prepared by the above preparation method.

[0016] Finally, the application of the above-mentioned carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material in the preparation of sodium ion battery positive electrode also falls within the protection scope of the present invention.

[0017] The present invention uses the prepared carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material as the positive electrode material to prepare a button battery, and measures the electrical properties of the button battery at 0.2C, 0.33C, and 1C current densities, respectively, and performs cycling at 1C current density to measure its 1C cycle stability. The results show that the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material prepared by the present invention exhibits excellent cycle stability.

[0018] It can be seen that the preparation method of the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material provided by the present invention can obtain carbon quantum dots by controlling the hydrothermal reaction conditions. The material has good conductivity, and then a nickel-iron-manganese-based hydroxide precursor is prepared by an intermittent co-precipitation method. The precursor is mixed with a sodium source and roasted to obtain a mixed-phase sodium ion battery positive electrode material. The carbon quantum dots and the mixed-phase sodium ion battery positive electrode material are evenly mixed in a solvent, filtered and dried to obtain a composite coating material, which not only improves the conductivity and structural stability of the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material, but also does not affect the electrochemical properties of the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material itself, thereby effectively improving the rate performance and cycle stability of the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material.

[0019] Compared with the prior art, the present invention has the following advantages: (1) The raw materials for preparing the positive electrode material of the present invention are widely available, the preparation method is simple, the production cost is low, and it is easy to produce on a large scale; (2) The mixed-phase sodium ion battery positive electrode material of the present invention has a P2 and O3 mixed-phase structure, and the two phase structure units are evenly and alternately distributed on a micrometer scale. This deep mixed-phase structure can inhibit the occurrence of irreversible phase change and improve the overall structural stability of the material; therefore, the electrochemical performance of the material is improved in addition to the cycle stability, and the rate performance and material capacity are also improved; (3) The method of the present invention is coated in a liquid phase environment, which ensures that the carbon quantum dots are evenly coated on the surface of the mixed-phase sodium ion battery positive electrode material. The method is simple and the coating effect is good. The obtained carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material has good crystallinity and stable structure. (4) The positive electrode material of the present invention is a mixed-phase sodium ion battery positive electrode material coated with carbon quantum dots. The coated material largely inhibits the side reaction between the mixed-phase sodium ion battery positive electrode material and the electrolyte, and reduces the reversible Na + loss; and carbon quantum dots have the advantages of high carrier migration rate, good thermal stability and chemical stability. The use of carbon quantum dots to coat the mixed-phase sodium-ion battery positive electrode material can improve the rate performance of the mixed-phase sodium-ion battery positive electrode material and improve the cycle performance. At the same time, it also plays a good role in isolating the nickel-iron-manganese-based sodium-ion battery positive electrode material and the electrolyte, which is beneficial for the mixed-phase sodium-ion battery positive electrode material to maintain its structural stability, so that the material has ultra-high rate performance and cycle stability, and can be used as a sodium-ion battery positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the SEM image of the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material prepared in Example 1.

[0021] Figure 2This is the XRD spectrum of the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material prepared in Example 1. DETAILED DESCRIPTION

[0022] The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, but not for limiting the scope of the present invention.

[0023] The experimental methods in the following examples are all conventional methods unless otherwise specified.

[0024] The quantitative tests in the following examples were all repeated three times, and the results were averaged.

[0025] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0026] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the art can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be purchased commercially.

[0027] Example 1 (1) Preparation of nickel-iron-manganese-based hydroxide precursor A nickel-iron-manganese-based hydroxide precursor is prepared by a coprecipitation method, wherein the molar ratio of nickel, iron and manganese in the nickel-iron-manganese-based hydroxide precursor is 1:1:1; wherein the raw materials of the nickel-iron-manganese-based hydroxide precursor are nickel sulfate, ferrous sulfate and manganese sulfate, the complexing agent is ammonia water, and the precipitant is sodium hydroxide; the reaction temperature is 60°C, the start-up base liquid is a mixed solution of ammonia water and sodium hydroxide, the pH value is 11.9, and the ammonia concentration is 6.5g / L; the pH value of the start-up base liquid is adjusted by sodium hydroxide; The specific preparation method is as follows: 2 mol / L sulfate solution and 4 mol / L sodium hydroxide solution are prepared according to the molar ratio of nickel, iron and manganese elements of 1:1:1; the sulfate solution and the sodium hydroxide solution are both prepared at a flow rate of 5 L / h, and a hydroxide precursor is prepared by coprecipitation method, and a solid black powder is obtained after washing and drying, which is a nickel-iron-manganese-based hydroxide precursor, and its molecular formula is Ni 0.33 Fe 0.33 Mn 0.33 (0H)2.

[0028] (2) Preparation of mixed phase sodium ion battery cathode materials The nickel-iron-manganese-based hydroxide precursor prepared as above is used as a raw material, the nickel-iron-manganese-based hydroxide precursor is mixed with sodium carbonate (the molar ratio of the nickel-iron-manganese-based hydroxide precursor to the sodium element in the sodium carbonate is 1:0.67 (P2 phase) or 1:0.95 (O3 phase)), and then TiO2 and ZrO2 are added, mixed in a high-speed mixer, and stirred at a uniform speed of 3000 rpm for 30 minutes to make the mixture evenly mixed; wherein, with the mass of the nickel-iron-manganese-based hydroxide precursor as a reference, the Ti element is doped with 2000 ppm and the Zr element is doped with 2000 ppm; the mixed material is transferred to a sagger and placed in a box-type atmosphere furnace and roasted at 950°C for 15 hours; the roasting atmosphere is an air atmosphere, and the roasting heating rate is 2°C / min. After cooling, the calcined material is taken out, and through crushing and screening, two types of nickel-iron-manganese-based sodium ion battery positive electrode materials, P2 phase and O3 phase, are obtained according to different sodium carbonate ratios; the P2 phase and O3 phase positive electrode materials are mixed in a mass ratio of 1:4 to obtain a mixed-phase sodium ion battery positive electrode material; (3) Preparation of carbon quantum dots 100 mL of 20% by mass ethylenediaminetetraacetic acid aqueous solution was placed in a polytetrafluoroethylene-lined high-pressure stainless steel reactor, and carbon quantum dots were prepared by hydrothermal method at a hydrothermal temperature of 200 °C for 2 h. The concentrated solution was concentrated by evaporation and crystallization (80 °C), and dried in a vacuum drying oven at 200 °C to obtain carbon quantum dot solid powder.

[0029] (4) Preparation of carbon quantum dot-coated mixed-phase sodium-ion battery cathode materials The carbon quantum dot solid powder and the mixed-phase sodium ion battery positive electrode material (based on the total mass of the mixed-phase sodium ion battery positive electrode material coated with the carbon quantum dots, the carbon content contributed by the carbon quantum dots is 0.1wt%) are dissolved in anhydrous ethanol solvent (solid content is 50wt%), 10L / min nitrogen is introduced, stirred for 1h, and naturally settled, the upper liquid is extracted, the remaining concentrated slurry material is filtered, and dried in an oven at 200°C to obtain the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material.

[0030] Figure 1 This is an SEM image of the carbon quantum dot-coated mixed-phase sodium-ion battery positive electrode material prepared in this example.

[0031] Figure 2 This is the XRD spectrum of the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material prepared in this example.

[0032] Example 2 The preparation method is the same as that of Example 1, except that the calcination temperature in step (2) is 900°C.

[0033] Example 3 The preparation method is the same as that of Example 1, except that the calcination temperature in step (2) is 850°C.

[0034] Example 4 The preparation method is the same as that of Example 1, except that the calcination temperature in step (2) is 800°C.

[0035] Example 5 The preparation method is the same as that of Example 1, except that the calcination temperature in step (2) is 1000°C.

[0036] Comparative Example 1 The preparation method is the same as that of Example 1, except that in this comparative example, during the process of coating the positive electrode material with carbon quantum dots, only the P2 phase material is selected for coating.

[0037] Comparative Example 2 The preparation method is the same as that of Example 1, except that in the process of coating the positive electrode material with carbon quantum dots in this comparative example, only the O3 phase material is selected for coating.

[0038] Comparative Example 3 The preparation method is the same as that in Example 1, except that: in this comparative example, only P2 phase material is used to prepare the positive electrode material of the sodium ion battery, and the P2 phase material is not coated with carbon quantum dots.

[0039] Comparative Example 4 The preparation method is the same as that in Example 1, except that: in this comparative example, only O3 phase material is used to prepare the positive electrode material of the sodium ion battery, and the O3 phase material is not coated with carbon quantum dots.

[0040] Comparative Example 5 The preparation method is the same as that of Example 1, except that steps (3) and (4) are omitted, that is, the P2 phase and O3 phase positive electrode materials are only mixed in a mass ratio of 1:4 to obtain a mixed-phase sodium ion battery positive electrode material, and the mixed-phase positive electrode material is not coated with carbon quantum dots.

[0041] Embodiment 6, performance test The 2016 model button cell was prepared as follows: The positive electrode sheet is prepared by mixing positive electrode material, conductive carbon black and binder polyvinylidene fluoride (PVDF) in a mass ratio of 90:5:5, using N-methylpyrrolidone (NMP) as a solvent to prepare a slurry, uniformly coating it on an aluminum foil, drying it at 120° C. and rolling it to a thickness of 300 μm, and vacuum drying it at 120° C. for 12 hours to obtain a positive electrode sheet. The positive electrode materials are prepared from Examples 1 to 5 and Comparative Examples 1 to 5, respectively.

[0042] The negative electrode uses a metallic sodium sheet, the separator is a polypropylene porous membrane, the electrolyte is a 1 mol / L NaPF6 solution, and the solvent is ethylene carbonate (EC) + diethyl carbonate (DEC) + dimethyl carbonate (DMC), with a volume ratio of EC:DEC:DMC of 1:1:1.

[0043] The discharge capacity of the prepared button cell was measured at current densities of 0.2C, 0.33C and 1C, and the cycle stability was measured at a current density of 1C for 50 cycles with a voltage range of 2-4V. The test results are shown in Table 1.

[0044] Table 1 Performance test results

[0045] As can be seen from Table 1, compared with Comparative Examples 1-5, the button cell with the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material prepared in Example 1 as the positive electrode material shows excellent rate performance and cycle stability, and maintains 98.70% for 50 cycles at a rate of 1C; indicating that the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material provided by the present invention is particularly suitable as a cyclic sodium ion battery positive electrode material, and the electrical performance of the mixed phase is greatly improved compared to the pure P2 phase or pure O3 phase positive electrode material. Compared with the positive electrode material of Comparative Example 5 in which the mixed-phase sodium ion positive electrode material is not coated with carbon quantum dots, Example 1 shows better gram capacity and cycle stability. The present invention adopts a liquid phase coating method to enhance the uniformity of the coating agent on the positive electrode surface, and the carbon quantum dot coating can inhibit the occurrence of side reactions between the positive electrode material and the electrolyte, thereby improving the electrical properties of the positive electrode material. Compared with Comparative Examples 1-5, the coating of carbon quantum dots in Example 1 is conducive to the material to exert a higher gram capacity and enhance the cycle performance of the material. Comparison of Examples 1-5 shows that the positive electrode material has the best electrical performance when the calcination temperature is 950°C. This temperature condition is conducive to controlling the crystal form of the sodium ion battery material and regulating the size growth and dispersion and agglomeration of the material during the sintering process.

Claims

1. A method for preparing a carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material, characterized in that: The steps include: (1) A nickel-iron-manganese-based hydroxide precursor, a sodium source and a dopant are mixed and calcined, and P2 phase and O3 phase sodium ion battery positive electrode materials are prepared by setting different proportions of the sodium source; (2) mixing the P2 phase and O3 phase sodium ion battery positive electrode materials to obtain a mixed phase sodium ion battery positive electrode material; (3) Dissolving the carbon quantum dot powder and the mixed-phase sodium ion battery positive electrode material in a solvent and stirring the mixture to obtain a solid which is the mixed-phase sodium ion battery positive electrode material coated with the carbon quantum dots.

2. The method for preparing a carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material according to claim 1, characterized in that: In step (1), when the molar ratio of the nickel-iron-manganese-based hydroxide precursor to the sodium in the sodium source is 1: (0.5-0.7), a P2 phase sodium ion battery positive electrode material is obtained; when the molar ratio of the nickel-iron-manganese-based hydroxide precursor to the sodium in the sodium source is 1: (0.8-1), an O3 phase sodium ion battery positive electrode material is obtained; The sodium source is sodium carbonate and / or sodium hydroxide; The dopant is a metal oxide of at least one of Al, Ca, Mg, Ti, Cu, Zn and Zr; The added amount of the dopant is 500-5000 ppm of the mass of the nickel-iron-manganese-based hydroxide precursor.

3. The method for preparing a carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material according to claim 1, characterized in that: In step (1), the calcination temperature is 500-1100°C; specifically, 800-1000°C; more specifically, 950°C; The calcination is carried out in an air atmosphere; The calcination time is 8-15 hours; the calcination heating rate is 2-10°C / min.

4. The method for preparing a carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material according to claim 1, characterized in that: In step (2), the mass ratio of the P2 phase and the O3 phase sodium ion battery positive electrode material is (0.2-2):1; In step (3), the carbon content contributed by the carbon quantum dots is 0.01 wt% to 0.3 wt% based on the total mass of the mixed-phase sodium ion battery positive electrode material coated with the carbon quantum dots; The solvent is anhydrous ethanol and / or tetrahydrofuran; The stirring time is 0.5 to 2 hours.

5. The method for preparing a carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material according to claim 1, characterized in that: In the nickel-iron-manganese-based hydroxide precursor, the molar ratio of nickel element, iron element and manganese element is 1:0.5~1.5:0.5~1.5; The nickel-iron-manganese-based hydroxide precursor is prepared by a coprecipitation method.

6. The method for preparing a carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material according to claim 1, characterized in that: The carbon quantum dots are prepared by a hydrothermal method; Specifically, the method for preparing the carbon quantum dots comprises the following steps: preparing at least one of citric acid, ethylenediaminetetraacetic acid and L-cysteine ​​into an aqueous solution, and performing a hydrothermal reaction to obtain the carbon quantum dots.

7. The method for preparing a carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material according to claim 6, characterized in that: The mass percentage concentration of the aqueous solution is 20% to 80%; The temperature of the hydrothermal reaction is 150-200° C. and the time is 2-15 hours.

8. A mixed-phase sodium ion battery positive electrode material coated with carbon quantum dots prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the carbon quantum dot-coated mixed-phase sodium ion battery positive electrode material according to claim 8 in preparing a sodium ion battery positive electrode.

Citation Information

Patent Citations

  • Layered positive electrode material of energy storage secondary battery and preparation method of layered positive electrode material

    CN114464789A

  • Layered positive electrode material of sodium-ion battery and application of layered positive electrode material

    CN115528226A

  • Preparation method and application of two-phase symbiotic structure sodium ion battery positive electrode material

    CN116598468A

  • Layered oxide composite positive electrode material and preparation method and application thereof

    CN117038908A

  • Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery

    CN117457887A

Cited By

  • Composite electrode, preparation method thereof and all-vanadium redox flow battery

    CN120637510A